Trypanosoma cruz i: Fosfolipasa A1 y lípidos como antígenos relevantes en la enfermedad de Chagas - Bott, Emanuel (2018)
Amastigotes, the replicative stage of Trypanosoma cruzi in the mammalian host, can infect macrophages and form amastigotes´ nests that when degenerate lead to inflammatory processes with the release of parasitic enzymes. Phospholipids can be modified by the action of phospholipases and generate bioactive lipids that could modulate the immune response. Here we show that T. cruzi Phospholipase A1 (PLA1) induced per se a pro-inflammatory response in macrophages. On the other hand, the lipid extracts of amastigotes from RA and K98 strains (RA and K98) and those obtained from lysed and incubated parasites (RAinc and K98inc) to allow the action of enzymes such as PLA1 on endogenous phospholipids, differentially induced macrophage M1/M2 activation parameters between RA vs. RAinc and K98 vs. K98inc, which could be attributed to quantitative variations of lysophospholipids and fatty acids, known bioactive lipids. The participation of TLR 2-6 in the inflammatory response induced by RA, RAinc, K98 and K98inc was determined. The present results highlight the discriminatory role of TLRs in the recognition of lipids derived from T.cruzi, with the consequent activation of signal transduction pathways in which NF-?B participates and is regulated by PPAR?? during the development of an inflammatory response.